Marketing Strategies for Small and Medium Enterprises in Rural Areas - Haris, Abdul (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study investigates marketing strategies for small and medium enterprises (SMEs) in rural areas, focusing on leveraging local resources, community-based marketing, and digital integration to enhance competitiveness and sustainability. Research Design and Methodology: The research employs a qualitative approach through a comprehensive literature review. This review synthesizes findings from existing studies on rural SME marketing to identify effective practices and strategies. Findings and Discussion: The findings reveal that leveraging local resources enhances product authenticity and sustainability, aligning with rural consumers' cultural values. Community-based marketing builds trust and loyalty through local engagement and participation in community activities. Despite challenges like the digital divide, digital integration allows SMEs to expand their reach and improve customer engagement via social media, e-commerce, and digital advertising. The study highlights the effectiveness of a hybrid marketing strategy that combines traditional and digital approaches. Implications: The study suggests the need for digital infrastructure improvements and targeted training to enable rural SMEs to utilize digital tools effectively. Support programs tailored to rural contexts are essential for implementing these strategies successfully. Future research should explore hybrid marketing strategies' long-term impacts and adaptability in various rural settings.